A liberdade de consntruir família como direito fundamental: a questão das uniões homoafetivas - Oliveira, Emanoella Rodrigues Remigio de (2010)
This study aims to examine the possibility of legal recognition of new forms of families arising from the union between same-sex. Assuming that society calls for a new structure in the provision of legal relations, and a new structure in the satisfaction of the right claimed, this research aims to draw parallels between the trajectory of the legal rules that govern family relations and new social arrangements that constitute the contemporary family as a result of new concepts established by the society of the century XXI, yet because of the state have the responsibility to adapt the means and ends, in order to ensure the best and full application of the law. Seek to identify the new concept of family, from the art. 226 of the Federal Constitution and Constitutional Principles, attached to the plurality of identifiable social arrangements. Moreover, it presents the concern in establishing these new legal rules of family law in line with the social reality of Brazil, to ensure full access to justice and respect for the principle of equality and freedom in interpersonal relations